MEASURES TO PROTECT BREEDING AND PRODUCTIVE CATTLE FROM PYROPLASMIDOSIS - Rasulov U.I; Bobonazarov E; Ilyasov Z.I (Scholar Express Journals, 2021)
The article discusses piroplasmidosis of cattle, which causes serious damage to livestock in the country. It also provides information on the origin and treatment of these diseases.
Keywords: Pedigree; productive cattle; farm; canals